Leitura e discurso: uma análise discursiva dos sujeitos leitores inscritos em um livro didático de língua portuguesa do ensino médio - Silva, Tarcilane Fernandes da (2019)
According to Angela Kleiman, “every text can in principle favor critical reflection; on the other hand, every text can also be trivialized by schoolwork ” (KLEIMAN, 2007, p. 105). Thus, it is in the inadequate way of approaching texts within the school that we find the biggest obstacles to the development of a satisfactory work with reading activity. In the present research, we aimed to analyze the reading conceptions and the profile of the reading subjects (student and teacher) enrolled in the didactic collection "Português Linguagens" of the 3rd year of high school. In order to anticipate the profile of these readers projected in the manual, we have taken works with editions ranging from 1990 to 2013. In order to delimit the investigation, our focus of analysis will turn to the approach that the authors take about the genre “comic strips”, in the activities proposed to the reader-student subject to work with this genre. This research fits into the theoretical perspective of pecheutian discourse analysis, based on it, we take the PL collection in order to foresee this reader by the textual objectality and the discourses that emerge from the authorial didactic project of each book. Imbued with this view, we realize that all the traits that appear in the constitution of textbook result from “previous discursive processes (coming from other conditions of production) that ceased to function, but gave rise to implicit“ decision making ”that ensures the possibility of the process discursive focus ” (PÊCHEUX, 1997, p. 85). Thus, nothing contained in the textbook is without reason; There is a raison d'être for all the diagrammatic, linguistic, and structural details of this artifact. Nothing in it is chosen at random: the authors of the texts addressed, the genres employed, the proposed activities, what is spoken or silenced, all make up the book for a specific reason. From this perspective, the activities of textual interpretation, much more than a means of exploring the reading of the text, bring the projection of the reader profile that one wants to be formed in school. “They are an explicit way of proposing that students produce their discourse, performing, with their prior knowledge, the characteristics of their socio-economic-cultural belonging, certain articulations between the various texts and their modalities” (MARTINS, 2007, p. 45). After the analysis of the corpus, the results showed the projection of a reader without critical sense, without idea, servile, who does not have the opportunity to weave the senses of the text through a constitutive memory. In the short historical-temporal outline of just over twenty years that we made of PL, it was also possible to delineate the profile changes that the teaching profession suffered especially in the 90s, motivated by the educational public policies instantiated in the country. These results prove that all the compositions that make up the discursive materiality of the textbook are the result of tensions between history, memory and ideology, materialized in an artifact from which the conceptions of text, reading, student and teacher can be anticipated.